Synthesis and antibacterial study of organotin(IV) complexes containing hydrazinopyridine ligand [Sintesis dan kajian antibakteria kompleks organostanum(IV) yang mengandungi ligan hidrazinopiridin] - Dayang Norafizan, Awang Chee; Monica Lulo, Rodis; Norziah, Saat; Zainab, Ngaini; Ainaa Nadiah, Abd Halim (The Malaysian Analytical Sciences Society, 2017)
Nowadays, the studies on organotin(IV) complexes with hydrazone ligand become more interesting due to their potential in various applications including medicinal area. In our recent studies, four new organotin(IV) complexes MeSnCl2(C12H12N4) (2), BuSnCl2(C12H12N4) (3), PhSnCl2(C12H12N4) (4) and Ph2SnCl(C12H12N4) (5) were synthesized by the direct reaction of methyl-2-pyridylketone-2-hydrazinopyridine ligand (1) and organotin(IV) chloride(s) in absolute methanol. These complexes have been characterized by UV-Visible, FT-IR, 1H and 13C NMR spectroscopies. All of the synthesized compounds were screened for antibacterial activity against Escherichia coli and Staphylococcus aureus. However, the complexes showed weak activity against the bacteria compared to the free ligand.